Conservation planning in agricultural landscapes: hotspots of conflict between agriculture and nature. Issue 3 (26th December 2014) - Shackelford, Gorm E.; Steward, Peter R.; German, Richard N.; Sait, Steven M.; Benton, Tim G.; Richardson, David
Abstract Aim Conservation conflict takes place where food production imposes a cost on wildlife conservation and vice versa. Where does conservation impose the maximum cost on production, by opposing the intensification and expansion of farmland? Where does conservation confer the maximum benefit on wildlife, by buffering and connecting protected areas with a habitable and permeable matrix of crop and non‐crop habitat? Our aim was to map the costs and benefits of conservation versus production and thus to propose a conceptual framework for systematic conservation planning in agricultural landscapes. Location World‐wide. Methods To quantify these costs and benefits, we used a geographic information system to sample the cropland of the world and map the proportion of non‐crop habitat surrounding the cropland, the number of threatened vertebrates with potential to live in or move through the matrix and the yield gap of the cropland. We defined the potential for different types of conservation conflict in terms of interactions between habitat and yield (potential for expansion, intensification, both or neither). We used spatial scan statistics to find 'hotspots' of conservation conflict. Results All of the 'hottest' hotspots of conservation conflict were in sub‐Saharan Africa, which could have impacts on sustainable intensification in this region. Main conclusions Systematic conservation planning could and should be used to identify hotspots of conservation conflict in agricultural landscapes, at multiple scales. The debate between 'land sharing' (extensive agriculture that is wildlife friendly) and 'land sparing' (intensive agriculture that is less wildlife friendly but also less extensive) could be resolved if sharing and sparing were used as different types of tool for resolving different types of conservation conflict (buffering and connecting protected areas by maintaining matrix quality, in different types of matrix). Therefore, both sharing and sparing should be prioritized in hotspots of conflict, in the context of countryside biogeography.